Is Posner Right? An Empirical Test of the Posner Argument for Transferring Health Spending from Old Women to Old Men - Johannes Schwarze; Christoph Wunder (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Posner (1995) proposes the redistribution of health spending from old women to old men to equalize life expectancy. His argument is based on the assumption that the woman's utility is higher if her husband is alive. Using self-reported satisfaction measures from a long-running German panel survey, the Socio-Economic Panel Study (SOEP), the present study conducts an empirical test of this assumption. Our matching-based estimation reveals satisfaction trajectories of women who experience the death of their spouse and identifies the causal effect of widowhood. The average level of satisfaction in a control group of non-widowed women serves as a reference to measure the degree of adaptation to widowhood. The results suggest bereavement has no enduring effect on satisfaction, and that is evidence against Posner's assumption.
Keywords: C14; D10; I31; 330; widowhood; adaptation; subjective well-being; life satisfaction; satisfaction with household income; propensity score matching; Ältere Menschen; Alleinlebende; Zufriedenheit; Sterblichkeit; Geschlecht; Gesundheitskosten; Deutschland